Advances in Clinical Sample Preparation for Identification and Characterization of Bacterial Pathogens Using Metagenomics - Bachmann, Nathan L.; Rockett, Rebecca J.; Timms, Verlaine Joy; Sintchenko, Vitali (Frontiers in Public Health, 2018)
Whole genome sequencing (WGS) plays an increasing role in communicable disease control through high-resolution outbreak tracing, laboratory surveillance and diagnostics. However, WGS has traditionally relied on microbial culture in order to obtain pathogen specific DNA for sequencing. This has severely limited the application of whole genome sequencing on pathogens with fastidious culturing requirements. In addition, the widespread adoption of culture-independent diagnostic tests has reduced availability of cultured isolates for confirmatory testing and surveillance. These recent developments have created demand for the implementation of techniques enabling direct sequencing of microbial genomes in clinical samples without having to culture an isolate. However, sequencing of specific organisms from clinical samples can be affected by high levels of contaminating DNA from the host and other commensal microorganisms. Several methods have been introduced for selective lysis of host cells and/or separate specific organisms from a clinical sample. This review examines the different approaches for sample preparation that have been used in diagnostic and public health laboratories for metagenomic sequencing.